STRATEGI KOMUNIKASI POLITIK PASANGAN BAMBANG-ICEK DALAM PEMILIHAN UMUM KEPALA DAERAH KABUPATEN GROBOGAN TAHUN 2011 - ARISTA NARENDRA, ROSA (Program Magister Ilmu Politik, Universitas Diponegoro, 2012)
Abstract In the general election of regional head of central java in 2010 and 2011, has held elections in 25 districts/municipalities of 35 districts/cities, 7 countries/cities of which are incumbent re-elected (won). Judging from the result of valid votes, the appeareance of the incumbent as the winner in teh district election Grobogan, this is the result of hard work from the personal as well as full support team of successful couples Bambang-Icek, so it gets a positive appreciation of the community because voters have choosen a partner back Bambang Pudjiono and Icek Baskoro is in the lead as the regent and deputy regent Grobogan district 2011. The problem formulation of research is how political communication strategies Bambang-Icek couples do in the General Election District Grobogan 2011? The results showed that the winning strategy Bambang-Icek (incumbent) can not be separated from the preparation of personal and political role of the bearer. Keywords: Strategy, Political Communication, Election, Incumbent Winning.